2018
DOI: 10.21608/zvjz.2018.7621
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunostimulant Activity of Spirulina platensis (Arthrospira platensis) and Sage (Salvia officinalis) in Nile Tilapia (Oreochromis niloticus)

Abstract: Immunostimulants have been found to be attractive and promising agents for disease management in aquaculture. The current study aimed to assess the impacts of feeding with Spirulina platensis (SP) and Salvia officinalis (SO) for 28 days on the immune status of Nile tilapia (Oreochromis niloticus). A total of 180 Nile tilapia (30.6 ± 0.12 g) were divided into 3 groups (triplicates of 20 fish/group). Control group was fed on a basal diet only, while the other two groups were supplemented with SP (10 gm/kg diet) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The growth promoting effects of ORG could be related to its aromatic flavour, which makes it a strong appetizer. The feed intake induced by flavour of ORG could eventually improve fish growth (Abdel-Latif & Khalil, 2014). In addition, the growth promoting effects of ORG may also be attributed to some bioactive compounds in the biochemical composition of ORG, which stimulate the secretion of digestive enzymes and following increases in food consumption and absorption (Radhakrishnan, Saravana Bhavan, Seenivasan, Muralisankar, & Shanthi, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth promoting effects of ORG could be related to its aromatic flavour, which makes it a strong appetizer. The feed intake induced by flavour of ORG could eventually improve fish growth (Abdel-Latif & Khalil, 2014). In addition, the growth promoting effects of ORG may also be attributed to some bioactive compounds in the biochemical composition of ORG, which stimulate the secretion of digestive enzymes and following increases in food consumption and absorption (Radhakrishnan, Saravana Bhavan, Seenivasan, Muralisankar, & Shanthi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of oregano includes high content of polyphenols, thymol and carvacrol, which have been recognized to have antioxidant effects (Lagouri et al 1993;Taimidou & Boskou, 1994). Several studies have shown the immunostimulating and antioxidant role of oregano in fish (Zheng, Tan, Liu, Zhou, Xiang, & Wang, 2009;Abdel-Latif & Khalil, 2014;Haghighi & Rohani, 2015;Diler, Gormez, Diler, & Metin, 2017;Beltrán, Espinosa, Guardiola, & Esteban, 2018), However, there are no information regarding the protective effects of oregano in relation to ROS resulting from pesticide-induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Phytobiotics enhance the fish's immune system by increasing the presence of immune markers such as immunoglobulin M (IgM), nitric oxide and lysozyme. For example, Abdellatief et al ( 108 ) revealed that a combination of sage ( Salvia officinalis ) and Spirulina platensis ( Arthrospira platensis ) can boost the immune system of Nile tilapia by increasing their immune response against Pseudomonas aeruginosa . Furthermore, phytobiotics, in the form of antioxidant compounds such as phenols and polyphenols, are beneficial for fish health by improving the immune system of aquatic animals against A. hydrophila ( 109 ).…”
Section: Phytobiotics Enhanced Aquaculture Species Tolerance Against Masmentioning
confidence: 99%
“…Several herbal compounds have been shown to modulate immune responses and treat infections. Plants from the Lamiaceae family (mints) have been studied in several recent experiments [ 60 , 66 , 67 , 68 , 73 , 74 ]. One study by Abdellatif et al reported a significant effect of combined sage ( Salvia officinalis ) and Spirulina platensis ( Arthrospira platensis ) on levels of immune markers, including lysozyme, nitric oxide, and immunoglobulin M (IgM), as well as increased resistance against Pseudomonas aeruginosa in Nile tilapia [ 68 ].…”
Section: The Effect Of Herbal Extracts and Plant Components On Immune-related Genes In Fish Speciesmentioning
confidence: 99%
“…Plants from the Lamiaceae family (mints) have been studied in several recent experiments [ 60 , 66 , 67 , 68 , 73 , 74 ]. One study by Abdellatif et al reported a significant effect of combined sage ( Salvia officinalis ) and Spirulina platensis ( Arthrospira platensis ) on levels of immune markers, including lysozyme, nitric oxide, and immunoglobulin M (IgM), as well as increased resistance against Pseudomonas aeruginosa in Nile tilapia [ 68 ]. Another study revealed a significant effect of 10 g/kg rosemary ( Salvia rosmarinus ) leaf on serum catalase and lysozyme activities, the alternative complement pathway, and resistance against Aeromonas hydrophila in the Nile tilapia [ 73 ].…”
Section: The Effect Of Herbal Extracts and Plant Components On Immune-related Genes In Fish Speciesmentioning
confidence: 99%